The Perception of Selected Grade-12 HUMSS Students of Bestlink College of the Philippines: Impact of the Gadgets: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to identify the impact of the gadgets on the students' academicperformance of the selected grade-12 HUMSS students in Bestlink College of the Philippines.From the result of the study, the gadget helps the students improve their written examination,academic performance, and performance tasks.The study recommended encouraging students to prioritize schoolwork before playing withtheir gadgets. Also, inspires students to believe that gadgets can benefit them. We also needto know your limitations on gadgets.
Keywords: Education